Artificial intelligence: reflections in philosophy, theology, and the social sciences - Göcke, Benedikt Paul; Rosenthal-von der Pütten, Astrid (Schöningh, Fink and mentis Religious Studies, Theology and Philosophy E-Books Online, Collection 2020, ISBN: 9783657100224, 2020)
Front Matter --Copyright page --Introduction /Benedikt Paul Göcke and Astrid Rosenthal-von der Pütten --Consciousness --Conscious, Thinking, and Intelligent Machines? /Tobias Müller --Deus Malignus - The Digital Rehabilitation of Deception /Walther Ch. Zimmerli --Artificial Intelligence of the Human Mind /Daniel Neumann --When Robots (pretend to) Think /Davide Ghiglino and Agnieszka Wykowska --Revisiting the Dancing-Qualia Argument for Computationalism /Stefan Reining --Superintelligence --Will Superintelligence Take Over? /Kilian Karger --Why Artificial Intelligence is a Matter of Design /Andreas Theodorou --Between Epistemic Progress and Existential Risk Minimization /Julia Alessandra Harzheim --Ethics --Current Challenges in Ethics of Artificial Intelligence or: Old Wine in New Bottles /Leonie Seng --Is Utilitarianism Entirely Useless for Self-Driving Car Ethics? /Vanessa Schäffner --The Car's Choice: Illusions of Agency in the Self-Driving Car Trolley Problem /Rebecca Davnall --Why Machines That Talk Still Do Not Think, and Why They Might Nevertheless be Able to Solve Moral Problems /Lukas Brand --Robots --Could Artificial General Intelligence be an End-In-Itself? /Benedikt Paul Göcke.